The Bahamas : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for The Bahamas. (IMF Staff Country Reports; Country Report, 2021)
The economic impact of COVID-19 on The Bahamas is unprecedented. The archipelago was just recovering from the devastation of Hurricane Dorian in the fall of 2019, when the pandemic led to a sudden stop in tourism, the main source of income and employment. The authorities mounted a rapid emergency response to support the economy and vulnerable households and put in place strict containment measures. But amid limited testing and health resources, reopening the economy has been challenging.